Chronic nonmalignant gynaecological pelvic pain - Önal, S. Ateş (My University, 2003)
Chronic pelvic pain is a complex problem with diverse etiology, and laparoscopy forms an important diagnostic and therapeutic tool. Unfortunately, pelvic pain is hard to measure, assess or localise, causing great difficulties in diagnosis and treatment, as well as frustration in both patients and physicians. In the absence of any visible pathology, management of pain may have a role in improving life quality in women with chronic pelvic pain. Despite the challenge inherent in the management of chronic pelvic pain, many patients can be treated successfully. Effective treatment modalities are available to lessen the impact of pain and offer reasonable expectations of an improved functional status. The purpose of this review is to emphasize the need for an integrated, multidisciplinary approach to the diagnosis and treatment of chronic nonmalignant gynaecological pelvic pain.
Kanser dişi jinekolojik kronik pelvik a?ri
Keywords: Chronic nonmalignant gynaecological pelvic pain; Diagnosis; Management